HUBUNGAN PENERAPAN TARIF JASA SIMPAN GADAI TERHADAP KEPUASAN NASABAH DI PEGADAIAN SYARIAH CABANG LANGSA - Tarlis, Andi; Aini, Wardatul; Junaidi (Jurnal Investasi Islam, 2019)
This study aims to determine the relationship between the application of pawning saving service rates to customer satisfaction at the Pegadaian Shari'ah Langsa Branch. In this study, researchers used a type of descriptive research that is the method used to look for the elements, characteristics, characteristics of a phenomenon. Data collection techniques in this study were observation, interviews and documentation. The results of the research in the ï¬ eld show that the application of pawn service deposit rates at Pegadaian Syariah Langsa Branch is in accordance with the wishes of the community. This was revealed by customers who stated that they had no objection to the applied tariffs so there was no doubt about conducting transactions at the Langsa Branch Pegadaian Syariah. Then the relationship between the application of pawning service tariffs to customer satisfaction at the Pegadaian Syariah Langsa Branch went well. The relationship between the application of pawning saving tariffs to customer satisfaction is that the customer is more interested in the amount of loan money received than the savings service obtained, then the process is also not complicated which can make customers bored and desperate waiting for the results to be provided by the Langsa City Pawnshop. Then customer satisfaction with the application of pawning deposit service rates at the Pegadaian Syariah Langsa Branch can be seen from the community's interest in conducting pawn transactions. This is inï¬‚ uenced by fast, easy and friendly service. Then the promos given by Pegadaian as well as cashback or gift giving offered also attract customers by Pegadaian Langsa City. In addition, the pawnshop itself always prioritizes customer satisfaction in interacting in the Langsa City pawnshop. Satisï¬ ed customers can increase company stability. Satisfaction with services can increase the existence of a customer's mind and gain trust.